Mapping learning difficulties in general chemistry course - Asyti Febliza; Putri Ade Rahma Yulis (Jurnal Pendidikan Kimia (JPKim), 2018)
Abstract:       Many first semester students in University struggle to study chemistry, it proven by low achievement of students in learning general chemistry. This study investigated student’s difficulties to understand in term of chemistry material characteristics (fundamental concept, advanced concept, mathematical concept and misconception) and learning process in the class. This investigation includes a coginitve test and a difficulty questionnaire were given to 92 first semester students in Biology program Universitas Islam Riau-Indonesia who took general chemistry course. Research questions in this study were: 1) What topics did students find difficult?; 2) Which chemistry material indicators did students feel difficult?; 3) How did student’s perceptions about learning chemistry before and after learning process in college?. The result gave information that student’s difficulties mostly existed in average level in chemical bonding about 84 students, stoichiometry around 52 students and higher level of barrier in colligative properties topics reached 52 students. Furthermore, students felt higher difficult in three indicators in term of mathematical concept, advanced concept and misconception with number reached 46%, 65% and 61% respectively. Difficulty questionnaire showed the slightly dropping around 9% before and after learning process. Overall, the difficulties encountered in average level and higher level. Topic that sudents felt difficult were: chemical bonding, stoichiometry and colligative properties, which each topic contained higher skill such as advanced concept, mathematical skill and misconception. The minor dip in student’s perception can give us information about quality changes after learning process.Keywords:basic chemistry; learning difficulties indicator; student’s difficulties; students’s perception